2014
DOI: 10.1007/s00170-014-6607-8
|View full text |Cite
|
Sign up to set email alerts
|

Research on the cold plasma jet assisted cutting of Ti6Al4V

Abstract: A long, quasi-homogeneous cold plasma jet was generated through a homemade cold plasma jet generating device. Friction-wear test and assisted cutting of Ti6Al4V were studied under air, nitrogen, and nitrogen cold plasma jet (NPJ) atmospheres. The friction coefficient under nitrogen jet was small, and the wear appearance was smooth at lowspeed friction. At high-speed friction, the friction coefficient under NPJ was the smallest, which declined by 70 % compared with that under air atmosphere. The scratches and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The friction coefficient was nearly 60% lower than that in air and the graphitization temperature of the diamond was increased by 38.9% by NPJ treatment. Liu et al [170] conducted a theoretical and experimental study on the PAC of Ti6Al4V. The results indicated that the machinability of Ti6Al4V could be remarkably improved with the assistance of a cold plasma jet.…”
Section: Cold Plasma Assisted Cuttingmentioning
confidence: 99%
“…The friction coefficient was nearly 60% lower than that in air and the graphitization temperature of the diamond was increased by 38.9% by NPJ treatment. Liu et al [170] conducted a theoretical and experimental study on the PAC of Ti6Al4V. The results indicated that the machinability of Ti6Al4V could be remarkably improved with the assistance of a cold plasma jet.…”
Section: Cold Plasma Assisted Cuttingmentioning
confidence: 99%
“…The material is sprayed directly into the cutting zone so that chemical affinity between the toolworkpiece interface is reduced. Furthermore, the plasma acts as a lubricant, thus reducing the built-up edge and decreasing the thermal generation in the cutting zone, as shown in figure 32 [29,40,103,104].…”
Section: Plasma Assisted Cutting Processmentioning
confidence: 99%
“…The Fe x C y N z is then adsorbed into the workpiece surface. During the cutting process, the complex thermal actions between the toolworkpiece contact interface also induce the reactive ions to generate new compounds, such as Fe(CO) 2 (NO) 2 and Fe (2/3/4) N, as shown in equations (3) and (4) [105].…”
Section: Plasma Assisted Cutting Processmentioning
confidence: 99%
See 1 more Smart Citation